Food as a Power: Ketergantungan Impor Beras Indonesia dalam Geo Ekonomi Global - Yakhin Oktoryanta Surbakti (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Rice is not merely a food commodity but also an instrument of power in the global political-economic order. This article examines how Indonesia’s dependence on rice imports places the country in a vulnerable position amid the increasingly fragmented dynamics of the global geoeconomy. Using a library research method, the study analyzes Indonesia’s rice production, consumption, and import data from 2019 to 2025 and relates them to the theoretical frameworks of food security, food geopolitics, and economic dependency theory. The findings indicate that the reduction of paddy fields, climate change, and high per capita rice consumption are the main structural drivers of imports. At the same time, geopolitical factors—such as export restrictions imposed by India and other major rice-producing countries—have exacerbated vulnerabilities in Indonesia’s national rice supply chain. Previous studies have largely focused on econometric analyses of the effects of rice imports on domestic prices and market stability, without explicitly linking these issues to the logic of power within the global food trade system. This article addresses that gap by positioning rice as a geoeconomic instrument, serving both as a source of bargaining power and as a point of weakness for national sovereignty. The findings underscore the need for strategies such as diversifying import sources, strengthening government food reserves, revitalizing irrigation infrastructure, and promoting diversification of carbohydrate consumption as forms of structural mitigation rather than merely short-term reactive policies.